2017
DOI: 10.1038/s41598-017-05133-2
|View full text |Cite
|
Sign up to set email alerts
|

Divergent secular trends in blood pressure and body mass index in children and adolescents in Hong Kong

Abstract: Secular trends in blood pressure (BP) and body mass index (BMI) during childhood and adolescence are sentinels for the future population cardiovascular disease burden. We examined trends in BP z-score (ages 9–18 years from 1999 to 2014) and BMI z-score (ages 6–18 years from 1996 to 2014) in Hong Kong, China. Overall, BP z-score fell, systolic BP from 0.08 to −0.01 in girls and from 0.31 to 0.25 in boys. However, the trends were not consistent, for both sexes, systolic BP z-score was stable from 1999, decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…These results are notable because the 19-year-old examinees were rarely affected by the use of BP medications and other comorbidities. Similarly, from 1996 to 2014, adolescents aged 9–18 years in Hong Kong showed an intensified BMI-SBP association over time, despite the discrepancy between BMI and SBP 14 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These results are notable because the 19-year-old examinees were rarely affected by the use of BP medications and other comorbidities. Similarly, from 1996 to 2014, adolescents aged 9–18 years in Hong Kong showed an intensified BMI-SBP association over time, despite the discrepancy between BMI and SBP 14 .…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, the strength of the BMI-BP association decreased over time in some studies 11 13 , whereas it increased in other studies 14 . Its association was still under debatable among previous studies because heterogeneous factors such as age, sex, and race could contribute to conflicting results.…”
Section: Introductionmentioning
confidence: 93%
“…Using the international body mass index cut-offs for children and youth, 36 the prevalence of obesity (including overweight) is relatively consistent across studies in Hong Kong 8 , 12 , 30 , 37 , 38 . For example, 22.4% of boys and 14.0% of girls were overweight or obese in 2014 37 . A cohort study indicated that the prevalence of overweight and obesity was stable across three annual assessment waves for primary school children 12 .…”
Section: Discussionmentioning
confidence: 94%
“…Each child carried a unique identification number to be tracked and had their identity kept anonymous. The participation rate of SHS was around 83.4% [19]. Details of the survey have been reported elsewhere [20].…”
Section: Methodsmentioning
confidence: 99%